Constructive Character-Based Problem Solving to Enhance Students’ Learning Outcomes in Physics Subject - Susilawati, Anggi; Faradilla, Meriza; Utama, Reka Julia (Unnes Science Education Journal, 2023)
The purpose of this study is for investigating whether constructive character-based problem solving can enhance students learning in physics subject. This study utilized quasi experiment by research design was equivalent control group design. The sample of this study was 28 students of grade IX which were divided into two groups. The first group was experimental class with 14 students who receive constructive character-based problem-solving learning. The second group was experimental class with 14 students who receive conventional learning with constructive character. The results obtained that based on students’ learning outcomes in the experimental class, the percentage value is 88.4% higher than the control class which is only 56.9%. Meanwhile for the constructivist character in the experimental class is also higher by 80% and in the control class by 68.5%. For the value of hypothesis test which has been conducted is obtained the tcount value is 2.247 > ttable 1.67. This means that problem solving learning based on constructivist characters has an impact on students learning outcomes in physics subject. With the result that it can be concluded that problem solving learning based on constructivist character is more effective to be implemented for enhancing students learning outcomes in physic subject.